2013
DOI: 10.1111/pace.12172
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Hemodynamic Response Using a Quadripolar LV Lead

Abstract: A quadripolar lead offers multiple additional pacing options to increase CO acutely compared to conventional bipolar leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Consequently the obesity did not diminish the clinical benefit of CRT-d to reduce risk for appropriate ICD therapy, as we observed in our study [36]. This effect, and the opportunity to program multiple LV pacing configurations, may be induced by multipolar pacing [37]. The multipolar stable, and continuous biventricular pacing, may induce a stabilization effect on cellular membranes, ionic currents, and cardiac cells [37].…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Consequently the obesity did not diminish the clinical benefit of CRT-d to reduce risk for appropriate ICD therapy, as we observed in our study [36]. This effect, and the opportunity to program multiple LV pacing configurations, may be induced by multipolar pacing [37]. The multipolar stable, and continuous biventricular pacing, may induce a stabilization effect on cellular membranes, ionic currents, and cardiac cells [37].…”
Section: Discussionmentioning
confidence: 49%
“…This effect, and the opportunity to program multiple LV pacing configurations, may be induced by multipolar pacing [37]. The multipolar stable, and continuous biventricular pacing, may induce a stabilization effect on cellular membranes, ionic currents, and cardiac cells [37]. This effect, reducing AF episodes PNS, LV lead dislodgments, and re-interventions to re-position LV leads, may be associated to a lowering of hospitalizations for HF worsening in T2DM failing heart patients [n 15 (15.2%) vs 24 (25%), p value 0.046], comparing multipolar pacing vs bipolar pacing (Table 4; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, quadripolar leads have been introduced. While serving to address high pacing thresholds and phrenic nerve stimulation issues, the multiple pacing configurations can also result in better hemodynamic response than standard, distal biventricular stimulation . Using bioimpedance, Osca et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that compared bipolar with quadripolar leads for CRT showed improved acute LV lead implantation success rate, shorter implantation time and lower fluoroscopy dose with quadripolar leads 5–6 . Furthermore, CRT with an IS‐4 lead tends to provide better clinical outcome and performance parameters 7–10 . However data on long‐term clinical outcome and adverse event rates are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6] Furthermore, CRT with an IS-4 lead tends to provide better clinical outcome and performance parameters. [7][8][9][10] However data on long-term clinical outcome and adverse event rates are necessary.…”
Section: Introductionmentioning
confidence: 99%